Desertification Assessment for the Marshes Region Using Soil Quality Indicators, Southern Iraq - Ahmed Al-Yasiry; Alaa Al-Lami; Ali Al Maliki (Iraqi Geological Journal, 2023)
The study aims to conduct an assessment of desertification in the marshlands of southern Iraq by using eight soil indicators. The study area is part of the governorates of Amarah, Basrah and Nasiriyah, with an area of about 27,989 km2. The Mediterranean model of desertification and land use model (MEDALUS) was adopted for the assessment of the soil quality indicators. Satellite image processing of Landsat images and ArcGIS v.10.7 programs were used to analyze different data and produce the soil quality index and maps for evaluating marshes area desertification. This study found that the marshes area is divided into two categories. The first category represented about 3.52%, covering a small area of 984 km2 and classified as non-sensitive to desertification. While the second category represents about 96.48%, covers most of the study area and involves 27.005 km2 and consider sensitive to desertification.